2020
DOI: 10.26596/wn.202011257-73
|View full text |Cite
|
Sign up to set email alerts
|

Commercial food advertising on the campus of Ghana’s largest University

Abstract: Background Non-Communicable Diseases (NCDs) are a leading cause of death globally. NCD mortality attributable to unhealthy food environments (FEs) is significant. Heavy marketing of unhealthy foods is an important contributor to unhealthy FEs. Aims We examined the extent of commercial food advertising, messaging, and signage on the campus of Ghana’s oldest and largest university. Methods We cross-sectionally collected data on all sighted advertisements. Advertisements/si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…According to the records of the Education Management Information System (EMIS) of the Ghana Education Service, the Greater Accra region had a total of 862 public primary schools and 812 public junior high schools in 2018 (65). Sampling 200 schools will give us 80% statistical power to compare a hypothesized outdoor unhealthy food marketing rate of 47% with the recently observed rate of 57% (21). In calculating the sample size for this aspect of the study, we hypothesized that the rate of outdoor marketing of unhealthy food will be 47% in comparison with a previously observed rate of 57% (21).…”
Section: Assessments At the Sub-national Levelsmentioning
confidence: 98%
See 2 more Smart Citations
“…According to the records of the Education Management Information System (EMIS) of the Ghana Education Service, the Greater Accra region had a total of 862 public primary schools and 812 public junior high schools in 2018 (65). Sampling 200 schools will give us 80% statistical power to compare a hypothesized outdoor unhealthy food marketing rate of 47% with the recently observed rate of 57% (21). In calculating the sample size for this aspect of the study, we hypothesized that the rate of outdoor marketing of unhealthy food will be 47% in comparison with a previously observed rate of 57% (21).…”
Section: Assessments At the Sub-national Levelsmentioning
confidence: 98%
“…Sampling 200 schools will give us 80% statistical power to compare a hypothesized outdoor unhealthy food marketing rate of 47% with the recently observed rate of 57% (21). In calculating the sample size for this aspect of the study, we hypothesized that the rate of outdoor marketing of unhealthy food will be 47% in comparison with a previously observed rate of 57% (21). Whereas, the study by Amevinya et al (21) was conducted in a highly urbanized university setting, this study would involve six districts (which include urban, peri-urban, and rural areas).…”
Section: Assessments At the Sub-national Levelsmentioning
confidence: 99%
See 1 more Smart Citation
“…This situation could promote the replacement of water with sugar-sweetened drinks which were sold for a similar price. The danger here is that children generally may consume less than their fluid requirements and be at risk of voluntary dehydration [25]. Proper hydration of children is known to have positive impacts on mood and cognition [38], and schools must provide pupils with free clean drinking water.…”
Section: Plos Onementioning
confidence: 99%
“…An expert assessment of government action on implementation of healthy food environment policies in Ghana concluded that implementation was insufficient [23]. There is also reported concentration of unhealthy foods and beverages in formal establishments in urban Ghana [24] with high evidence of the dominance of unhealthy foods in commercial advertisements in higher education [25]. Literature on how pupils interact with the prevailing food retail environment at schools in Ghana is limited [3,4].…”
Section: Introductionmentioning
confidence: 99%